Identification of investment attraction strategies to increase the economic potential of a trading enterprise - A. Loi (Economics, Entrepreneurship, Management, 2023)
In the current conditions of globalisation and rapid development of market competition, effective investment attraction is becoming a critical success factor for enterprises in the trade sector. The purpose of this study is to analyse ways to attract investment in the development of the economic potential of commercial enterprises and substantiate the areas for potential development. In the course of the study, methods of statistical analysis of enterprise reporting data, methods of abstraction and generalisation were used. The paper discusses such strategies as the active use of digital technologies for business promotion, focus on startups and innovative projects, environmental responsibility and social orientation of businesses, new methods of attracting investment, such as crowdfunding and the use of cryptocurrency and blockchain technologies, and attracting corporate investments and partnerships. Various areas of attracting investment were compared, including bank lending, private placement of shares, initial public offering of shares, and raising venture capital. These advantages and disadvantages of each area help businesses understand which approach might be most appropriate for their specific needs. The factors influencing the choice of investment attraction strategy for commercial enterprises are considered. First of all, the company must define its goals and needs for investment, analyse the market situation, assess financial stability and solvency, and assess risks and potential profitability. Next, the company can choose the most suitable investment attraction tool in accordance with its goals and market conditions. The company METRO Cash and Carry Ukraine is analysed as one of the leaders among commercial enterprises in Ukraine. METRO Cash and Carry Ukraine uses an innovative policy of investing in economic potential, actively raising funds for automation and optimisation of activities, and uses leasing to expand its network with minimising risks. In general, attracting investment is very important for the growth of an enterprise and the successful implementation of its economic potential, the choice of investment attraction strategy is crucial for the growth of trading enterprises, helping to secure the necessary financial resources and increase their competitiveness